Benefits of not smoking during pregnancy for Australian Aboriginal and Torres Strait Islander women and their babies: a retrospective cohort study using linked data. Issue 11 (21st November 2019) - McInerney, Carol; Ibiebele, Ibinabo; Ford, Jane B; Randall, Deborah; Morris, Jonathan M; Meharg, David; Mitchell, Jo; Milat, Andrew; Torvaldsen, Siranda
Abstract : Objectives: To provide evidence for targeted smoking cessation policy, the aim of this study was to compare pregnancy outcomes of Aboriginal mothers who reported not smoking during pregnancy with Aboriginal mothers who reported smoking during pregnancy. Design: Population based retrospective cohort study using linked data. Setting: New South Wales, the most populous Australian state. Population: 18 154 singleton babies born to 13 477 Aboriginal mothers between 2010 and 2014 were identified from routinely collected New South Wales datasets. Aboriginality was determined from birth records and from four linked datasets through an Enhanced Reporting of Aboriginality algorithm. Exposure: Not smoking at any time during pregnancy. Main outcome measures: Unadjusted and adjusted relative risks (aRR) and 95% CIs from modified Poisson regression were used to examine associations between not smoking during pregnancy and maternal and perinatal outcomes including severe morbidity, inter-hospital transfer, perinatal death, preterm birth and small-for-gestational age. Population attributable fractions (PAFs) were calculated using adjusted relative risks. Results: Compared with babies born to mothers who smoked during pregnancy, babies born to non-smoking mothers had a lower risk of all adverse perinatal outcomes including perinatal death (aRR=0.58, 95% CI 0.44 to 0.76), preterm birth (aRR=0.58, 95% CI 0.53 to 0.64) and small-for-gestational age (aRR=0.35, 95% CI 0.32 to 0.39). PAFs (%) were 27% for perinatal death, 26% for preterm birth and 48% for small-for-gestational-age. Compared with women who smoked during pregnancy (n=8919), those who did not smoke (n=9235) had a lower risk of being transferred to another hospital (aRR=0.76, 95% CI 0.66 to 0.89). Conclusions: Babies born to women who did not smoke during pregnancy had a lower risk of adverse perinatal outcomes. Rates of adverse outcomes among Aboriginal non-smokers were similar to those among the general population. These results quantify the proportion of adverse perinatal outcomes due to smoking and highlight why effective smoking cessation programme are urgently required for this population.